Ocular hypotensive effect and safety of travoprost 0.004%/timolol maleate 0.5% fixed combination after change of treatment regimen from ß-blockers and prostaglandin analogs - Inoue K (Dove Medical Press, 2012)
Kenji Inoue1, Akira Setogawa1, Risako Higa1, Ryo Moriyama1, Masato Wakakura1, Goji Tomita21Inouye Eye Hospital, Chiyoda-ku, Tokyo, Japan; 22nd Department of Ophthalmology, Toho University School of Medicine, Tokyo, JapanIntroduction: Travoprost 0.004%/timolol maleate 0.5% fixed combination eye drops are available in Japan. We prospectively investigated the intraocular pressure (IOP)-decreasing effect of travoprost 0.004%/timolol maleate 0.5% fixed combination eye drops and the adherence of patients to the administration protocol.Materials and methods: We studied 43 eyes from 43 patients diagnosed with primary open-angle glaucoma, who were using prostaglandin analogs and ß-blockers. The prostaglandin analogs and ß-blockers were discontinued, and the treatment regimen was changed to travoprost 0.004%/timolol maleate 0.5% fixed combination eye drops without any washout period. IOP before and at 1 month, 3 months, and 6 months after the treatment change was evaluated and compared. A questionnaire about protocol adherence was administered 1 month after the treatment change.Results: IOP was 15.7 ± 2.9 mmHg before the change, 15.5 ± 2.7 mmHg at 1 month after the change, 15.3 ± 3.6 mmHg at 3 months after the change, and 15.8 ± 3.2 mmHg at 6 months after the change, and none of the differences were significant (P = 0.191). The responses to the questionnaire showed that cases where eye drop administration was forgotten decreased after the treatment change. Moreover, because of changes in eye drops, 19.0% of patients had irritation. More than half (54.8%) of the patients preferred travoprost 0.004%/timolol maleate 0.5% fixed combination eye drops. Seven patients (16.3%) discontinued eye drop use because of adverse reactions within 6 months after the change.Conclusion: When the treatment regimen was changed from prostaglandin analogs and ß-blockers to travoprost 0.004%/timolol maleate 0.5% fixed combination eye drops, administration protocol adherence increased and IOP was preserved; however, adverse reactions appeared in about 16% of the cases.Keywords: travoprost 0.004%/timolol maleate 0.5% fixed combination, ß-blockers, prostaglandin analog, change, intraocular pressure